Originalism in Theology and Law: Comparing Perspectives on the Bible and the Constitution - Boone, Mark J. (Lexington Books/Fortress Academic, 2024)
According to originalism, the meaning of a text is determined at the time of its writing. Originalism in Theology and Law explores the similarities and differences between the theological application of this idea to the Bible and its legal application to the American Constitution.